Liberalism, Surveillance, and Resistance: Indigenous Communities in Western Canada, 1877-1927 - Keith Smith (The West Unbound:Social and Cultural Studies, 2009)
Canada is regularly presented as a country where liberalism has ensured freedom and equality for all. Yet with the expansion of settlers into the First Nations territories that became southern Alberta and BC, liberalism proved to be an exclusionary rather than inclusionary force. Between 1877 and 1927, government officials, police officers, church representatives, ordinary settlers, and many others operated to exclude and reform Indigenous people. Presenting Anglo-Canadian liberal capitalist values and structures and interests as normal, natural, and beyond reproach devalued virtually every aspect of Indigenous cultures. This book explores the means used to facilitate and justify colonization, their effects on Indigenous economic, political, social, and spiritual lives, and how they were resisted.